2020
DOI: 10.3390/nu12020329
|View full text |Cite
|
Sign up to set email alerts
|

Sesamol Alleviates Obesity-Related Hepatic Steatosis via Activating Hepatic PKA Pathway

Abstract: This study aimed to investigate the effect of sesamol (SEM) on the protein kinase A (PKA) pathway in obesity-related hepatic steatosis treatment by using high-fat diet (HFD)-induced obese mice and a palmitic acid (PA)-treated HepG2 cell line. SEM reduced the body weight gain of obese mice and alleviated related metabolic disorders such as insulin resistance, hyperlipidemia, and systemic inflammation. Furthermore, lipid accumulation in the liver and HepG2 cells was reduced by SEM. SEM downregulated the gene and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 53 publications
5
26
0
Order By: Relevance
“…Figure 4a The up-regulated PPARα and CPT-1A transcriptions were in line with the above results that the amounts of the TG and fat droplets in hepatocytes were lowered by sesamol intervention, suggesting that sesamol potently reduced intracellular fat accumulation by promoting lipolysis. These data agreed with previous publications that PPARα and CPT-1A levels for fatty acid β-oxidation were markedly increased by sesamol treatment in the liver of HFD-induced obese mice (Xu et al, 2020). Moreover, Qin et al (2019) reported that sesamol showed a positive effect on obesity-associated metabolic disorders by improving the expression of CPT-1A.…”
Section: Sesamol Up-regulates Gene Expressions Related To Fatty Acid Oxidationsupporting
confidence: 92%
“…Figure 4a The up-regulated PPARα and CPT-1A transcriptions were in line with the above results that the amounts of the TG and fat droplets in hepatocytes were lowered by sesamol intervention, suggesting that sesamol potently reduced intracellular fat accumulation by promoting lipolysis. These data agreed with previous publications that PPARα and CPT-1A levels for fatty acid β-oxidation were markedly increased by sesamol treatment in the liver of HFD-induced obese mice (Xu et al, 2020). Moreover, Qin et al (2019) reported that sesamol showed a positive effect on obesity-associated metabolic disorders by improving the expression of CPT-1A.…”
Section: Sesamol Up-regulates Gene Expressions Related To Fatty Acid Oxidationsupporting
confidence: 92%
“…Eight-week-old male C57BL/6J mice were obtained from Central South University (Hunan, Changsha, China) and maintained under standard laboratory conditions (20–24°C, 40–60% humidity, and light and dark cycle: 12 h/12 h). As previously described ( 25 ), the mice were given 1 week to allow them to adapt to the new environment and allowed free access to water and food. Then, one group was fed a normal-fat diet (NFD), forming the control group ( n = 10), and all other mice received a high-fat diet (HFD group) for 8 weeks to establish the obese model.…”
Section: Methodsmentioning
confidence: 99%
“…As previously described ( 25 ), after 16 weeks, blood samples were collected from the femoral artery of the mice and stored overnight at 4°C. Then the serum was separated by centrifuging the samples at 3,000 × rpm for 15 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…β3-AR, act as an isoform of the adrenergic receptor, initiates the activation of protein kinase A (PKA) [14]. It is well established that PKA is closely related to lipolysis [15], accomplished by activating the AMPK pathway, reducing lipid production, increasing fatty acid βoxidation, and bene cial for improving liver lipid metabolism [16]. AMPK is a universal metabolic sensor that has a crucial role in maintaining lipid homeostasis [17], regulate fatty acid β-oxidation by activating PGC-1α [18], Moreover, the activation of AMPK can also boost the expression of CD206, which is highly expressed in M2 macrophages [19], and transform macrophages from a pro-in ammatory M1 phenotype to an anti-in ammatory M2 phenotype, subsequent reduction the deleterious in ammation [20].…”
Section: Discussionmentioning
confidence: 99%